NIGERIA POLICE FORCE AND THE CHALLENGES OF INSECURITY IN NIGERIA: A STUDY OF RIVERS STATE, NIGERIA - Ihedioha, Chinyere Eucharia; Terna, Jimin Henry (Gapenas Publisher, 2024)
This study examined Nigeria Police Force and the Challenges of Insecurity in Nigeria: A study of Rivers State. The study adopted six (6) research questions, objectives and hypotheses and they constituted the study guide. The study adopted the descriptive survey research design to investigate the Nigerian Police Force and Challenges of Insecurity in Nigeria; Taro Yamane formula was used to determine the sample size and four hundred (400) respondents were randomly selected from three Local Government Areas in Rivers State namely, Ogba/Egbema/Ndoni, Emohua and Gokana. Frequency and simple percentage was used to analyze the data while Mean and the Spearman Rank Order Correlation were used to test the hypotheses. The findings reveal that there is problem of insecurity and crime in Rivers State, Nigeria with (grand mean of 2.69). It was also revealed that poverty, high rate of unemployment and underemployment of youths in the state, bad leadership/governance and corruption amongst other things are the major causes of insecurity in Rivers State with (grand mean of 3.44). It was further revealed that the shortage of crime fighting facilities by the Nigerian Police Force has a significant relationship with insecurity situation in Rivers State, Nigeria with (rho = 0.109, p = 0.04). However, the Nigerian Police Force is not equipped and empowered to tackle insecurity in Rivers State, Nigeria with (grand mean of 2.48).The study recommends amongst others that the Police Force should be well equipped to perform its functions well and in compliance with the rule of law; sensitization exercise should be taken as a priority in addressing relationship that exists between the public and personnel of the Nigerian Police Force